Aggressive Angiomyxoma in Pregnancy: A Rare Condition, a Common Misdiagnosis - J. Sampaio; I. Sarmento-Gonçalves; D. Ramada; T. Amaro; P. Tiago-Silva (Hindawi Limited, 2016)
Introduction. Aggressive angiomyxoma is a rare mesenchymal neoplasm. Although benign in the majority of the cases, these neoplasms usually present a locally infiltrative nature and high rates of recurrence. Due to its rarity, misdiagnosis is a common problem. Case Presentation. We present one case of aggressive angiomyxoma in a 25-year-old pregnant woman. The patient presented with a large vaginal mass that was interpreted as a vaginal cyst. We performed surgical resection of the neoplasm and the correct diagnosis was only achieved after histological examination. With this case, we highlight the importance of considering this diagnosis in patients with genital and perineal masses of unknown origin and the impact of a correct preoperative diagnosis in patient's management and follow-up. Conclusion. Although aggressive angiomyxoma is rare, it should be considered in differential diagnosis of pelviperineal masses in young women. Its positivity to estrogen and progesterone receptors can justify enlargement and recurrence during pregnancy, although few cases are reported. Early recognition demands high index of suspicion for both gynaecologists and pathologists. Wide surgical excision with tumor free margins is the basis of curative treatment. Adjuvant therapy may be necessary for residual or recurrent tumors. Long-term follow-up is recommended.